2020
DOI: 10.1002/qua.26234
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical infrared spectrum of the ethanol hexamer

Abstract: The hydrogen bond network of ethanol clusters is among the most complex hydrogen bond networks of molecular clusters. One of the reasons of its complexity arises from the number of possible ethanol monomers (there are three isoenergetic isomers of the ethanol monomer). This leads to difficulties in the exploration of potential energy surfaces (PESs) of ethanol clusters. In this work, we have explored the PES of the ethanol hexamer at the MP2/aug-cc-pVDZ level of theory. We have provided structures and their re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…Using 50‐mers, the solvation free energy of the proton in ammonia was calculated to be −277 kcal mol −1 at the M06‐2X/6–31++g(d,p) level of theory. Malloum also investigated other molecular clusters [254–256]. Huang found that the real and imaginary part of the effective permittivities of the pyridine (C 5 H 5 N)–ethanol (C 2 H 5 OH) mixture are larger than those of their pure components at some concentrations [257].…”
Section: Applicationsmentioning
confidence: 99%
“…Using 50‐mers, the solvation free energy of the proton in ammonia was calculated to be −277 kcal mol −1 at the M06‐2X/6–31++g(d,p) level of theory. Malloum also investigated other molecular clusters [254–256]. Huang found that the real and imaginary part of the effective permittivities of the pyridine (C 5 H 5 N)–ethanol (C 2 H 5 OH) mixture are larger than those of their pure components at some concentrations [257].…”
Section: Applicationsmentioning
confidence: 99%
“…In organic molecules, the atoms that make up chemical bonds or functional groups are constantly vibrating, and their vibration frequency is equivalent to that of infrared light 28 . Consequently, when the organic molecules are irradiated with infrared light, the chemical bonds or functional groups in the molecules can undergo vibrational absorption 29 .…”
Section: Resultsmentioning
confidence: 99%
“…In organic molecules, the atoms that make up chemical bonds or functional groups are constantly vibrating, and their vibration frequency is equivalent to that of infrared light. 28 Consequently, when the organic molecules are irradiated with infrared light, the chemical bonds or functional groups in the molecules can undergo vibrational absorption. 29 Different chemical bonds or functional groups have different absorption frequencies, and will be in different positions on the infrared spectrum, so the chemical bonds or functional groups contained in the molecules can be obtained.…”
Section: Synthesis and Thermal Stability Of P (Aapba-co-pte)mentioning
confidence: 99%
“…The ABCluster code has been successively used in our previous works on molecular clusters to generate initial structures for further optimization at a higher level of theory. [33][34][35][36][37][38][39][40][41][42][43][44] The reader can refer to those works or the original works of Zhang and Dol 31,32 for further details on the generation of the structures using ABCluster. In this work, the structures generated using ABCluster have been further optimized at the MP2/aug-cc-pVDZ level of theory.…”
Section: Methodsmentioning
confidence: 99%
“…The Tempo program has been first published by Fifen and co-workers 45 and the corrected version has been successfully applied to protonated ammonia clusters, 35,46,47 ammonia clusters 33,48 and acetonitrile clusters. 39,43 It should be noted that these probabilities could also be calculated by computing the free energies at different temperatures, G k T ð Þ, using the freqchk module of Gaussian 16 and reporting the results into the Equation (2). It is worth noting that the Boltzmann distribution is not valid for very low temperatures due to quantum effects.…”
Section: Methodsmentioning
confidence: 99%